Feasibility randomized-controlled trial of online acceptance and commitment therapy for painful peripheral neuropathy in people living with HIV: The OPEN study - Scott, Whitney; Guildford, Beth J.; Lwanga, Julianne; Williams, Amanda C de C; McCracken, Lance M. (European Journal of Pain, 2021)
Neuropathic pain negatively affects quality of life among people living with HIV (PLWH). This study examined the feasibility of conducting a full-scale randomized-controlled trial of online acceptance and commitment therapy (“ACT OPEN”) for neuropathic pain in PLWH. Using a parallel-groups design, thirty-eight participants were randomized to ACT OPEN or a waitlist control (2:1). Participants completed standard self-report outcome measures at baseline, and two- and five-months post-randomization. Participants were aware of their allocation, but assessment was blinded. Twenty-five participants were randomized to ACT OPEN and 13 to the control (of 133 referrals). ACT OPEN completion was 69% and two-month trial retention was 82%. Treatment credibility and satisfaction scores for ACT OPEN were comparable to scores reported in previous trials of cognitive-behavioural treatments for pain. Four adverse events were reported during the study, including one serious adverse event; all of these were unrelated to the research procedures. Small to moderate effects and 95% confidence intervals suggest that the true effect may favour ACT OPEN for improvements in pain intensity/interference and depression. A full-scale RCT of online ACT for pain management in PLWH may be feasible with refinements to trial design to facilitate recruitment.